ANALISIS STRATEGI INOVASI PRODUK DALAM MENGHADAPI PERSAINGAN PASAR PADA UMKM KERIPIK SAYUR YU MI - Iranda Juliawati (CV. Denasya Smart Publisher, 2025)
This study aims to determine the Analysis of Product Innovation Strategies in Facing Market Competition in Yu Mi Vegetable Chips MSMEs. This research uses a qualitative method with data collection techniques through interviews with five resource persons accompanied by observation to obtain more accurate information directly and documentation as evidence of research. The results showed that the product innovation strategy implemented by Yu Mi Vegetable Chips MSMEs includes new product development, product differentiation, attractive packaging design, and utilization of digital platform as promotional media. The strategy has a positive impact on competitiveness, customer loyalty, and business suistainability in the midst of intense competition.